1995
DOI: 10.1016/s1078-5884(05)80234-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postocclusion reactive hyperaemia, papaverine and nifedipine on duplex derived haemodynamic parameters of infrainguinal bypass grafts

Abstract: Duplex derived flow measurement of infrainguinal bypass grafts can evaluate graft and limb haemodynamics in the postoperative period. Pharmacological manipulations, such as vasodilation, can influence the physiological runoff with subsequent increase in volume flow through the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is known that vasodilating stimuli (eg, papaverine) are able to increase flow in bypass grafts. 33 In the study of Karacagil et al, 34 increase in PSV, mean velocity, and flow volume was found in autografts. 33 This effect has also been demonstrated in allograft bypasses, pointing to a decreased peripheral resistance causing an increased flow without change of diameter.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is known that vasodilating stimuli (eg, papaverine) are able to increase flow in bypass grafts. 33 In the study of Karacagil et al, 34 increase in PSV, mean velocity, and flow volume was found in autografts. 33 This effect has also been demonstrated in allograft bypasses, pointing to a decreased peripheral resistance causing an increased flow without change of diameter.…”
Section: Discussionmentioning
confidence: 90%
“…33 In the study of Karacagil et al, 34 increase in PSV, mean velocity, and flow volume was found in autografts. 33 This effect has also been demonstrated in allograft bypasses, pointing to a decreased peripheral resistance causing an increased flow without change of diameter. In the study of Boley et al, 35 collateral flow was studied in dogs during experimental reduction of SMA flow.…”
Section: Discussionmentioning
confidence: 90%
“…Previous papers describe changes in the flow volume in the reconstruction zone, both before and after application of vasodilatative substances. [12][13][14] With in situ bypasses, unligated side branches can be detected. 15 Stirnemann et al found that, in order for a reconstruction to remain open, vein bypasses require 10 ml/min minimum flow and PTFE bypasses require 50 ml/min.…”
Section: Discussionmentioning
confidence: 99%
“…1 The diameter of the bypass vein and the peripheral resistance also have an influence on the flow. 13,21 Ascer et al showed, that the outflow resistance predicts late patency of infrainguinal bypasses and limb salvage. 22,23 Intraoperatively, the application of vasodilatative substances into the bypass reduces the peripheral resistance and increases the flow.…”
Section: Discussionmentioning
confidence: 99%